A systematic analysis of the network of lncRNAs and mRNAs regulated by TP53 and TP53 mutants with hotspot mutations - Hong Chen; Zhongrong Guo; Peilong Li; Wanxiang Liao; Yunhao Li; Bo Li; Yan Li; Qingqing Zhu; Yingsi Lu; Lifen Huang; Xiaoyu Xu; Yunjun Xiao; et al. (Scientific Reports)
Abstract The transcription factor TP53 exhibits the preeminent frequency of genetic mutations across various cancer types. Long non-coding RNAs (lncRNAs) stand as pivotal molecules in the initiation and progression of carcinogenesis. Nonetheless, the specific roles of TP53-regulated lncRNAs in colon cancer remain largely unexplored. In this study, we conducted a comprehensive analysis of lncRNA and mRNA alterations in DLD1 colon cancer cells, induced by the overexpression of wild-type TP53, as well as two TP53 hotspot mutations, namely TP53-R175H and TP53-R175P, leveraging transcriptomic deep sequencing technology. Across all three experimental groups, large-scale datasets encompassing approximately 300 lncRNAs and 1000 mRNAs were identified. Integrative analyses, employing KEGG and Reactome functional annotations of differentially expressed lncRNA targets, coupled with enrichment of differentially expressed mRNAs, unveiled several shared downstream pathways. From this convergence, we curated a list of predicted TP53-regulated lncRNAs exhibiting differential expression patterns. Further pathway enrichments focusing on these lncRNAs converged on DNA replication and cell cycle processes, mirroring the well-established functions of TP53. Remarkably, lncRNA H19 and LINC00969 emerged as common denominators across all three cell groups, hinting at their potential as targets for further study in colon cancer. Collectively, our findings delineate the repertoire of potential TP53-regulated lncRNAs and their downstream signaling cascades in colon cancer cells, contingent upon TP53 overexpression or the presence of TP53-R175H/R175P mutations. This study underscores the intricacies of TP53 mutation functionality in colon tumorigenesis, orchestrated through multiple lncRNAs.